Oral lichen-planus-associated fibroblasts acquire myofibroblast characteristics and secrete pro-inflammatory cytokines in response to Porphyromonas gingivalis lipopolysaccharide stimulation - Liping Wang; Yinshen Yang; Xiaoqin Xiong; Ting Yu; Xinhong Wang; Wenxia Meng; Haiyan Wang; Gang Luo; Linhu Ge (BMC, 2018)
Abstract Background Oral lichen planus (OLP) is a chronic inflammatory oral mucosal disease in which comprehensive inflammation-related cytokines are involved. These cytokines are commonly produced by immune cells and specific nonimmune cells including keratinocytes, endothelial cells and fibroblasts. This raises the question of whether fibroblasts in OLP lesions contribute to the inflammatory process upon inflammatory simulation. Methods Primary cultured Oral lichen-planus-associated fibroblasts (OLP AFs, n = 5) and normal buccal mucosal fibroblasts (NFs, n = 5) were examined by immunohistochemistry, Western blotting and reverse transcription-polymerase chain reactions (RT-PCR). Various inflammatory mediators were evaluated with a multiplex assay. Differences among groups were assessed using a Student's test or repeated measures one-way ANOVA, as appropriate. Results OLP AFs express significantly higher levels of α-smooth muscle actin (α-SMA) than NFs, indicating the presence of myofibroblasts. Myofibroblasts secrete Interleukin (IL)-6, IL-8, and tumor necrosis factor-α (TNF-α) in response to Porphyromonas gingivalis lipopolysaccharide (pg. LPS). Conclusion OLP AFs demonstrated α-SMA expression and secreted pro-inflammatory cytokines in response to pg. LPS stimulation.